2012
DOI: 10.5897/ajb12.1698
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of genetic diversity in some durum wheat (Triticum durum Desf.) in Palestine

Abstract: Random amplified polymorphic DNA (RAPD) analysis was conducted to estimate the genetic diversity and relatedness among 10 wheat cultivars and landraces. Five out of 70 decamer random primers showed distinctly polymorphic bands when used to amplify genomic DNA. The primers yielded a total of 157 RAPD markers of which 150 were considered as polymorphic. Each primer produced 18 to 37 polymorphic bands with an average of 30 markers per primer. DNA fragments size ranged from 350 to 1910 bp. The mean similarity indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Phenotypic descriptors have been used to effectively characterise several crop genotypes, particularly in stressful environments [5,26,27,28]. However, most phenotypic descriptors particularly quantitative characters, are not very reliable as markers due to strong influence by genotype -environment interaction [29]. For this reason, analysis of diversity at the molecular level is used to validate and/or complement phenotypic characterization [5,30].…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic descriptors have been used to effectively characterise several crop genotypes, particularly in stressful environments [5,26,27,28]. However, most phenotypic descriptors particularly quantitative characters, are not very reliable as markers due to strong influence by genotype -environment interaction [29]. For this reason, analysis of diversity at the molecular level is used to validate and/or complement phenotypic characterization [5,30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, RAPD primers were able to distinguish taxa below the species level (Choo et al, 2009), since RAPD analysis reflects both coding and non-coding regions of the genome (Vanijajiva et al, 2005). Thus, it would not be surprisingly that RAPD was able to detect the genetic diversity among different plant species in Palestinian figs, Faba beans, wheat, …etc, using the same procedure with same or different primers that used in these studies (Al-Fares and Abu-Qaoud, 2012;Basheer salimia et al, 2012) In this study, the optimized RAPD procedure was able to distinguish clearly among the five different Thyme species where Primer OPD-19 was found to differentiate between any two Thyme species except Thymus incanus and Thymus capitatus. It was also observed that OPD-19 primer gave 2 unique bands for Thymus fruticosus.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to that, RAPD primers were able to distinguish taxa below the species level (Choo et al, 2009), since RAPD analysis reflects both coding and non-coding regions of the genome (Vanijajiva et al, 2005). Thus, it would not be surprisingly that RAPD was able to detect the genetic diversity among different plant species in Palestinian figs, Faba beans, wheat, …etc, using the same procedure with same or different primers that used in these studies (Al-Fares and Abu-Qaoud, 2012;Basheer salimia et al, 2012) In this study, the optimized RAPD procedure was able to distinguish clearly among the five different Thyme species where Primer OPD-19 was found to differentiate between any two Thyme species except Thymus incanus and Thymus capitatus. It was also observed that OPD-19 primer gave 2 unique bands for Thymus fruticosus.…”
Section: Discussionmentioning
confidence: 96%